Anomalies facial features and most common dental malposition men - Sánchez Riofrío, Diego; Sánchez Cifuentes, Abdón (Revista Universidad de Guayaquil, 2010)
A study was conducted with the purpose of obtaining information about facial features and dental malpositions anomalies more common in Ecuadorian mestizo men between 18-22 years of age. The results showed that the most common facial profile is straight profile and that there is a harmony between the middle and lower facial thirds. 20% had some type of lips incompatibility. From 25 casesstudied only one showed anterior open bite and none anterior cross bite. Patients had more crowdedteeth areas than diastemas and 4 cases of ectopic teeth were showed. As for the type of malocclusion 42% of the sample were Class I, Class II 0% and 25% bilateral Angle Class III, regarding 67% ClassI, Class II 0% and 4% Class III in bilateral canine relation. We conclude that the Ecuadorian mestizo men have in common a harmoniousfacial profile andoverjet and overbite measures within the norm,there is a high percentage of teeth loss in particular the 1st permanent molar, which translates intospace loss, occlusion problems and a poor masticatory function. It requiresthe participation of Dental Service to identify and correct bad oral habits at an early age and put emphasis on treatments that preserve these teeth considered by Angle as critical to the proper position and occlusion of thedental arch.
Keywords: Facial Profile; Crowded teeth; Diastemas; Lips Incompatibility; Angle Classification